Birth Environment Experiences Of Postnatal Mothers; An Exploratory Qualitative Study In Nalerigu, Ghana. - Alechana, J.A.; Ampofo, E.A.; Mumuni, A.A.; Dzantor, E.K.; Gbene, J. (Midwifery, 2025)
Problem: While there are many studies on women’s childbirth experiences globally, there is limited studies on childbirth experiences in Ghana especially in the North East Region. Background: The environment where women give birth is important, influences the birth process and outcomes of mother and neonate. Current understanding of influence birth environment and childbirth experiences in the northern parts of Ghana has not been fully explored. Study aim: Our study aimed at exploring the birth environment and mothers’ childbirth experiences in North-East Region, Ghana. Methods: An exploratory-descriptive qualitative (EDQ) study involving thirteen (Tzeng et al., 2017) purposefully selected postnatal mothers in Nalerigu was conducted. Using a semi-structured interview guide, individual face to-face in-depth tape-recorded interviews were conducted until data saturation. Interviews were transcribed verbatim and analysed using thematic analysis. Two (Afulani et al., 2019) main and 5 sub-themes emerged. Findings: The findings of the study revealed that birthing environment had an influence on mothers’ experiences with regards to comfort, and privacy. However, mothers reported that the environment did not offer options for choice to alternative birthing positions. It was observed that these environmental factors had both positive and negative effects on mothers during childbirth. Discussion & Conclusion: Study findings showed that the birth environment is associated with comfort, privacy, service provision satisfaction and desire for facility delivery and limited involvement in the choice of birth position. Though most of the participants indicated favourable birth environment and satisfactory services, it is important to address the concerns of the few who had negative experiences during labour to promote respectful maternity care. Antenatal education on birth positions is recommended.
Research Article
Keywords: Birth environment; Labour; Childbirth; Respectful maternity care